Pengaruh Suplementasi Vitamin C Terhadap Tingkat Stres Mahasiswa Fakultas Kedokteran Angkatan 2016 Universitas Ciputra - Alvionita Muntholib; Azimatul Karimah; Minarni Wartiningsih (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2021)
Introduction: Stress is an event that places a strain or demand on a person, disrupting the body's balance and physical and psychological conditions. Students often experience stress due to the numerous orders placed on them regarding learning and extracurricular activities on campus. Because medical students are prone to stress due to academic factors and the pressure they face, additional treatment is required to ensure that it does not have a long-term impact. Objective: This study aims to show that vitamin C supplementation can help medical students at Ciputra University feel less stressed. Method: A pre-and post-experimental study and the total sampling technique were used, and the respondents were divided into two groups: treatment and control. The DASS (Depression Anxiety Stress Scale) questionnaire was used in this study as the instrument. After that, the paired t-test was used to examine the data. The findings revealed that 66.6 percent of students in the pre-intervention experimental group experienced mild stress. In comparison, 29.16 percent of students in the pre-intervention control group had a normal pre-experimental score of 17.96. With an average result of 11.58, 95.8% of the participants in the post-intervention experimental group or after vitamin C supplementation were classified as usual. In a comparative test, the average stress score before and after supplementation differed significantly (p = 0.05). It can be concluded that supplementing with vitamin C can help students cope with stress.